Possible associations between antioxidant enzyme polymorphisms and metabolic abnormalities in patients with schizophrenia - Saruwatari J (Dove Medical Press, 2013)
Junji Saruwatari,1,* Norio Yasui-Furukori,2,* Ryoko Kamihashi,1 Yuki Yoshimori,1 Kentaro Oniki,1 Shoko Tsuchimine,2 Madoka Noai,1 Yasushi Sato,3 Taku Nakagami,4 Norio Sugawara,2 Manabu Saito,2 Akira Fujii,2 Ayami Kajiwara,1 Shuichi Mihara,5 Yasuhiro Ogata,6 Sunao Kaneko,2 Kazuko Nakagawa1,71Division of Pharmacology and Therapeutics, Graduate School of Pharmaceutical Sciences, Kumamoto University, Kumamoto, 2Department of Neuropsychiatry, Hirosaki University School of Medicine, Hirosaki, 3Department of Psychiatry, Hirosaki Aiseikai Hospital, Hirosaki, 4Department of Psychiatry, Odate Municipal General Hospital, Odate, 5Mihara Life Care Clinic, Kumamoto, 6Japanese Red Cross Kumamoto Health Care Center, Kumamoto, 7Center for Clinical Pharmaceutical Sciences, Kumamoto University, Kumamoto, Japan*These authors contributed equally to this paperBackground: This study investigated the possible association between common and potentially functional polymorphisms of antioxidant enzymes and metabolic abnormalities in patients with schizophrenia.Methods: The possible associations of the glutathione S-transferase (GST) M1 null and GSTT1 null genotypes, and the superoxide dismutase 2 (SOD2) Val16Ala polymorphism with the risks of being overweight and having metabolic syndrome were examined using a logistic regression analysis in 154 schizophrenic Japanese patients and 203 controls.Results: Among smokers with schizophrenia, the risks of being overweight and having decreased high-density lipoprotein cholesterol were significantly higher in those with the GSTM1 null genotype than in those with the present genotype (odds ratio 3.20 and 3.15, P=0.03 and P=0.04, respectively), while among nonsmokers with schizophrenia, the risk of an abnormal waist circumference was lower in those with the GSTM1 null genotype (odds ratio 0.34, P=0.04). The risk of a decreased high-density lipoprotein cholesterol level was significantly higher in patients with the combined GSTM1 null and GSTT1 present genotypes than in those with the present genotypes of both genes (odds ratio 3.60, P<0.01). The SOD2 Val16Ala polymorphism was not associated with risk of metabolic abnormalities in either group.Conclusion: The present study suggests that the GSTM1 null genotype, in combination with smoking status or GSTT1 genotype, might be associated with the metabolic abnormalities in patients with schizophrenia.Keywords: schizophrenia, metabolic syndrome, oxidative stress, glutathione S-transferase, superoxide dismutase 2, polymorphism